Disclosing the double mutualist role of birds on Galápagos - Olesen, Jens M. (2018)
Life on oceanic islands deviate in many ways from that on the mainland. Their biodiversity is relatively poor and some groups are well-represented, others not, especially not insects. A scarcity of insects forces birds to explore alternative food, such as nectar and fruit. In this way, island birds may pollinate and disperse seed to an extent unseen on any mainland; they may even first consume floral resources of a plant species and then later harvest the fruit of the same species. Through this biotic reuse, they may act as double mutualists. The latter have never been studied at the level of the network, because they are traditionally considered rare. We sampled pollination and seed-dispersal interactions on Galápagos and constructed a plant-bird mutualism network of 108 plant (12% being double mutualists) and 21 bird species (48% being double mutualists), and their 479 interactions, being either single (95%) or double mutualisms (5%). Double mutualists constitute the core in the pollination-dispersal network, coupling the two link types together. They may also initiate positive feedbacks (more pollination leading to more dispersal), which theoretically are known to be unstable. Thus, double mutualisms may be a necessary, but risky prerequisite to the survival of island biodiversity.